The impact of internal waves on upper continental slopes: insights from the Mozambican margin (southwest Indian Ocean). Issue 6 (5th February 2020) - Miramontes, Elda; Jouet, Gwenael; Thereau, Estelle; Bruno, Miguel; Penven, Pierrick; Guerin, Charline; Le Roy, Pascal; Droz, Laurence; Jorry, Stephan J.; Hernández‐Molina, F. Javier; Thiéblemont, Antoine; Silva Jacinto, Ricardo; et al.
Abstract: Evidences of sedimentation affected by oceanic circulation, such as nepheloid layers and contourites are often observed along continental slopes. However, the oceanographic processes controlling sedimentation along continental margins remain poorly understood. Multibeam bathymetry and high‐resolution seismic reflection data revealed a contourite depositional system in the Mozambican upper continental slope composed of a contourite terrace (a surface with a gentle seaward slope dominated by erosion) and a plastered drift (a convex‐shape sedimentary deposit). A continuous alongslope channel and a field of sand dunes (mainly migrating upslope), formed during Holocene, were identified in the contourite terrace at the present seafloor. Seismic reflection data of the water column show internal waves and boluses propagating in the pycnocline near the upper slope. The channel and the dunes are probably the result of the interaction of the observed internal waves with the seafloor under two different conditions. The alongslope channel is located in a zone where intense barotropic tidal currents may arrest internal solitary waves, generating a hydraulic jump and focused erosion. However, upslope migrating dunes may be formed by bottom currents induced by internal solitary waves of elevation propagating landwards in the pycnocline. These small‐scale sedimentary features generated by internal waves are superimposed on large‐scale contouritic deposits, such as plastered drifts and contourite terraces, which are related to geostrophic currents. These findings provide new insights into the oceanographic processes that control sedimentation along continental margins that will help interpretation of palaeoceanographic conditions from the sedimentary record. © 2020 The Authors. Earth Surface Processes and Landforms published by John Wiley & Sons Ltd Abstract : Internal waves are energetic processes capable of shaping continental slopes. Arrested internal waves by barotropic tidal currents may form channels. Bottom currents induced by internal solitary waves may generate upslope migrating dunes.